Respostas
respondido por:
1
(3x-2)² - (3x+2).(3x-2)=0
(3x-2)² - 9x²-6x+6x-4=0
9x²+4 - 9x² - 4 = 0
0=0
(4x-1)²/16 - x²=0
16x²-1/16 - x²= 0
16x²+1/16 - 16x²/16=0/16 corta os denominadores
16x²+1-16x²=0
1=0
Acho que é isso, perdão se errei.
(3x-2)² - 9x²-6x+6x-4=0
9x²+4 - 9x² - 4 = 0
0=0
(4x-1)²/16 - x²=0
16x²-1/16 - x²= 0
16x²+1/16 - 16x²/16=0/16 corta os denominadores
16x²+1-16x²=0
1=0
Acho que é isso, perdão se errei.
BIAHMJ:
obgg
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás